Dnipropetrovsk National University named after Oles’ Gonchar - Pakhomov, Olexandr (Acta Agraria Debreceniensis, 2010)
The Dnipropetrovsk National University is a multi-profile educational and scientific complex, where 16 faculties, the faculty of continuing education, the faculty of correspondence and distance education, post-graduate courses, doctorate, three scientific research institutes, 107 sub-faculties (departments) function, where about 1300 teachers including 150 Doctors of Science, professors and about 700 Candidates of Science, associate professors. In Dnipropetrovsk National University 15,000 students study majoring in 64 fields of knowledge and also foreign students and post-graduate students from more than 20 countries of the world study there. The educational and scientific process at the university correspond to the highest levels of the home and world standards.